PENINGKATAN LITERASI PERENCANAAN KEUANGAN BAGI PELAJAR DAN KELOMPOK USAHA MUDA UNTUK MENDUKUNG PEMBANGUNAN EKONOMI YANG INKLUSIF DAN BERKELANJUTAN - Ranila Suciati; Siti Hidayati; Kery Utami; R. Parianom; Hani Novanti (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
Young business groups in Indonesia face challenges in developing their enterprises, focusing on business growth and stability. One of the main obstacles they encounter is limited understanding of financial concepts and access to formal financial services. This research aims to enhance financial literacy and financial inclusion among young business groups through community service programs. The methods employed in this program include conducting financial planning literacy training focused on cash management, emergency fund management, and debt management. The program is conducted at the Youth Forum, Yayasan Panti Nugraha, South Jakarta, which partners in this initiative. The results of this community service initiative demonstrate a significant improvement in participants' understanding and readiness in managing their business finances. Participants show increased understanding in financial planning, risk management, and identifying key challenges faced by young business groups. Recommendations for further development include deepening participants' understanding in financial risk management, expanding collaboration networks with local and national financial institutions to enhance access to financial products, and conducting regular monitoring and evaluation of program implementation. These steps are expected to strengthen the financial capacity of young business groups and support sustainable business growth